From burnout to behavior: the dark side of emotional intelligence on optimal functioning across three managerial levels - Sariraei, Samira A.; Shkoler, Or; Giamos, Dimitris; Chênevert, Denis; Vandenberghe, Christian; Tziner, Aharon; Vasiliu, Cristinel (Frontiers in Psychology, 2024)
Introduction Burnout has been typically addressed as an outcome and indicator of employee malfunctioning due to its profound effects on the organization, its members, and its profitability. Our study assesses its potential as a predictor, delving into how different sources of motivation—autonomous and controlled—act as mediational mechanisms in the association between burnout and behavioral dimensions of functioning (namely, organizational citizenship behaviors and work misbehaviors). Furthermore, the buffering effects of emotional intelligence across three different managerial levels were also examined. Methods To this end, a total non-targeted sample of 840 Romanian managers (513 first-, 220 mid-, and 107 top-level managers) was obtained. Results Burnout predicted motivation, which predicted work behaviors in a moderated-mediation framework. Contrary to our initial prediction, emotional intelligence augmented the negative association between burnout and motivation, exhibiting a dark side to this intelligence type. These findings are nuanced by the three managerial positions and shed light on the subtle differences across supervisory levels. Discussion The current article suggests a relationship between multiple dimensions of optimal (mal)functioning and discusses valuable theoretical and practical insights, supporting future researchers and practitioners in designing burnout, motivation, and emotional intelligence interventions.